Penaeid prawn fishery and its maximum sustainable yield at Versova, Mumbai - Deshmukh, V D; Patkar, D S; Karnik, P C (Indian Journal of Fisheries, 2011)
Penaeid prawn fishery at Versova, Mumbai was investigated for the ten-year period of 1988 to 1997. The average annual catch during the period was 3,764 t, of which the trawlers contributed 84.9% and 15.1% by the dol nets. The major species contributing to the fishery were Parapenaeopsis stylifera (61.2%), Solenocera crassicornis (12.4%), Metapenaeus affinis (8.9%) and M. brevicornis (8.5%)’in trawlers andP. stylifera (51.5%),S. crassicornis (28.3%) andP. hardwikii (11.0%) in dol nets. Month wise abundance, size range, mean size, maturity and sex ratio in the two gears averaged for the period are discussed. Trawling at Versova commenced in 1986-’87 and due to encouraging returns many dol net owners also shifted over to trawling. Consequently the catch of penaeid prawns also increased from 1,363.71 in 1988 to 4,740.71 in 1996, and thereafter it declined considerably. Using Schaefer’s surplus yield model, maximum sustainable yield (MSY) and the related effort (FMSY) were estimated. The MSY was found to be 4,368.81 with the optimum effort of 3.75 X 105 hours of fishing for the dol nets and trawlers together, which corresponds to operation of 158 daily trawler trips and 38 dol net boats for the sustainable penaeid prawn fishery at Versova.